2023
DOI: 10.1038/s43018-023-00522-1
|View full text |Cite
|
Sign up to set email alerts
|

Disrupting the phase separation of KAT8–IRF1 diminishes PD-L1 expression and promotes antitumor immunity

Abstract: Immunotherapies targeting the PD-1/PD-L1 axis have become first-line treatments in multiple cancers. However, only a limited subset of individuals achieves durable benefits because of the elusive mechanisms regulating PD-1/PD-L1. Here, we report that in cells exposed to interferon-γ (IFNγ), KAT8 undergoes phase separation with induced IRF1 and forms biomolecular condensates to upregulate PD-L1. Multivalency from both the specific and promiscuous interactions between IRF1 and KAT8 is required for condensate for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 77 publications
0
20
0
Order By: Relevance
“…Moreover, the patients with lower 7NAS risk scores have a better response to immunotherapy and commonly have a long overall survival time compared to the patients high 7NAS risk scores underwent immunotherapy. IRF1 is the key transcription factor downstream of IFNg which can be induced by STAT1 (30,31). Here, in this study we demonstrated that IRF1 was most strongly correlated with the infiltration and functional roles of immune cells, suggesting it could serve as a potential target for enhancing the effectiveness of immunotherapy for SCLC patients.…”
Section: Discussionmentioning
confidence: 52%
“…Moreover, the patients with lower 7NAS risk scores have a better response to immunotherapy and commonly have a long overall survival time compared to the patients high 7NAS risk scores underwent immunotherapy. IRF1 is the key transcription factor downstream of IFNg which can be induced by STAT1 (30,31). Here, in this study we demonstrated that IRF1 was most strongly correlated with the infiltration and functional roles of immune cells, suggesting it could serve as a potential target for enhancing the effectiveness of immunotherapy for SCLC patients.…”
Section: Discussionmentioning
confidence: 52%
“…Third, it’s now well accepted that the enzymatic activity of cGAS can be inhibited by binding to chromatin nucleosome in the nucleus ( 14 ), however, whether cGAS participates in transcriptional regulation through modulating chromatin accessibility is unknown. LLPS has been previously reported to be important for regulating the activity of transcriptional factors such as IRF1 ( 129 ), and cGAS is capable of forming LLPS ( 23 ). Therefore, it’s interesting to question whether LLPS of cGAS serves as a mechanism underlying transcriptional regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Following procedures as previously described ( 71 ). To label L3MBTL2-interacting proteins, doxycycline-inducible Flag-Bio-ID-L3MBTL2–expressing U2OS stable cells were treated with doxycycline (200 ng/ml) for 24 hours.…”
Section: Methodsmentioning
confidence: 99%